Pylephlebitis and Crohn’s disease: A rare case of septic shock - Scaringi, Stefano (Int J Surg Case Rep, 2017)
INTRODUCTION: Troncular pylephlebitis, defined as septic thrombophlebitis of the portal vein, is usually secondary to suppurative infection from the regions drained by the portal system. Therefore, pylephlebitis can occur from the portal vein main tributaries. The occurrence of mesenteric pylephlebitis in Crohn’s disease is extremely rare. PRESENTATION OF CASE: We describe a case of septic shock due to mesenteric pylephlebitis in a 47 years old male affected with Crohn’s disease. The patient was admitted to the emergency department after he had been complained from 3 h of a peri-umbilical abdominal pain associated to fever and shivering quickly followed by a severe hypotension. His medical history included histologically confirmed ileal Crohn’s disease diagnosed 4 years before and treated with mesalamine only. Computed tomography scan confirmed the mesenteric pylephlebitis diagnosis. After medical therapy with antibiotics and systemic nutrition, the patient was successfully operated to treat his ileal Crohn’s disease. DISCUSSION: In our case, the quick onset of a septic shock was not due to a peritonitis complicating a Crohn’s disease, but to a rare condition not needing an urgent surgical resolution. This report shows that, even in Crohn’s disease, once diagnosis is performed, antibiotic therapy associated to enteral and parenteral nutrition can lead to a complete clinical remission of mesenteric pylephlebitis, mandatory to perform an elective surgery. CONCLUSION: This case highlights the importance of promptly considerate and treat mesenteric pylephlebitis in presence of a septic shock in a Crohn’s disease patient who is not showing clinical signs of peritonitis.